Nuclear Energy: A Keystone in Colombia's Sustainable Energy Transition - Galeano, David-Andrés; Muñoz , Jhon-Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article presents a comprehensive analysis of the potential integration and implications of Small Modular Reactors (SMRs) into Colombia's energy matrix, set against the backdrop of the global energy transition and the urgent need to address climate change. Focusing on the technical and technological aspects of nuclear energy, particularly SMRs, the study explores the advantages of nuclear power in terms of constant generation capacity and minimal carbon emissions, while also addressing public perception challenges and radioactive waste management. It delves into Colombia's current energy landscape, dominated by hydroelectric and thermal power, and highlights the need for diversification and resilience in the face of climatic and geopolitical challenges. The potential of SMRs in Colombia is scrutinized, considering their operational costs, environmental impact, and role in non-interconnected zones. Additionally, the article examines Colombia's historical and future trajectory in nuclear energy, emphasizing the importance of a robust regulatory framework, sustainable mining practices, public education, and awareness. The study concludes with strategic recommendations for Colombia, advocating for continuous training, international cooperation, exploration of economic opportunities, and investment in renewable energies alongside nuclear power to ensure a sustainable and diversified energy future.